Analysis of Causes and Intervention Design for the Papua Conflict based on Structural, Accelerator, and Trigger (SAT) Model - Chandra, Arlina Alfiani; Sukendro, Achmed; Uksan, Arifuddin; Widodo, Pujo; Anas, Muhammad Riza Fathu (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The Papua conflict remains unresolved and is one of Indonesia's enduring challenges. Special autonomy and development efforts by the government in the region have not succeeded in fostering peace. This study aims to explore the causes of the Papua conflict and provide insights into conflict intervention strategies using the Structural, Accelerator, and Trigger (SAT) Model. This qualitative research as defined by Sugiyono utilized secondary data analysis to gain comprehensive understanding of the conflict intervention design for Papua based on implications of Structural, Accelerator, and Trigger (SAT) Factors. Data was gathered from various sources including books, journals, government documents, and media articles related to the dynamics of the Papua conflict. The study found that by applying the Structural, Accelerator, and Trigger (SAT) Model, the underlying causes of the conflict can be delineated, paving the way for intervention strategies based on these causes. Structural causes such as trust issues with the government, economic inequality, and divergent interests need interventions such as trust building, sustainable economic policies, and negotiation. Accelerator causes such as mass media require interventions such as strengthening media ethics, while conflict triggers such as violence necessitate law enforcement through judicial measures to achieve sustainable peace in Papua.